Study of National Demonstration and Farmers' Education Programme - Planning Commission (Planning Commission, 1978)
Realising the need for demonstrating the efficacy of the new agricultural practices based on scientific knowledge, information and skill and channelising the results of research immediately to the farmers, the Government of India launched the National Demonstration Programme in April, 1965. This was followed by the Farmers Education and Training Programme initiated by the Directorate of Extension of the Ministry of Agriculture and Irrigation in 1966-67. In 1970 the two programmes were integrated in the districts which were common to both. It the instance of the Planning Commission the Programme Evaluation Organisation undertook an evaluation study of the National Demonstration and Farmers Education Programme in 1971-72.
Programme Evaluation Organisation Planning Commission Government of India